Revealing the impact of scientific culture understanding on students’ biological literacy: The role of digital mindfulness and local wisdom literacy - Asham Bin Jamaluddin; Muhiddin Palennari; Adnan Adnan; Evrialiani Rosba (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
The low level of biological literacy among students shows the importance of exploring and integrating the dimensions of scientific, cultural and digital understanding in learning. This study aims to analyze the influence of scientific culture understanding on students' biological literacy, by exploring the mediating role of digital mindfulness and local wisdom literacy. The study used a quantitative approach with an explanatory design and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. The sample consisted of 495 biology education students from three universities in Makassar, selected using a purposive sampling technique. The research instrument was a four point Likert scale closed questionnaire to measure four main constructs. The results of the analysis showed that scientific culture understanding had a significant effect on biological literacy directly and indirectly through digital mindfulness and local wisdom literacy. The strongest relationship was found between scientific culture understanding and local wisdom literacy, while the contribution of digital mindfulness was weak but significant. The R² value for biological literacy of 0.440 indicated a moderate model contribution. The conclusion of this study emphasizes the importance of integrating cultural, technological, and scientific approaches in biology learning in higher education. This study provides theoretical contributions to the development of local context based scientific literacy as well as practical recommendations for educators and policy makers in designing quality and effective curricula.Abstrak. Rendahnya tingkat literasi biologi di kalangan mahasiswa menunjukkan pentingnya untuk mengeksplorasi dan mengintegrasikan dimensi pemahaman sains, budaya dan digital dalam pembelajaran. Penelitian ini bertujuan untuk menganalisis pengaruh scientific culture understanding terhadap literasi biologi mahasiswa, dengan mengeksplorasi peran mediasi dari digital mindfulness dan literasi kearifan lokal. Penelitian menggunakan pendekatan kuantitatif dengan desain eksplanatori dan analisis Partial Least Squares Structural Equation Modeling (PLS-SEM). Sampel terdiri dari 495 mahasiswa pendidikan biologi dari tiga universitas di Makassar, yang dipilih menggunakan teknik purposive sampling. Instrumen penelitian berupa angket tertutup skala Likert empat poin untuk mengukur empat konstruk utama. Hasil analisis menunjukkan bahwa scientific culture Understanding berpengaruh signifikan terhadap literasi biologi secara langsung, maupun tidak langsung melalui digital mindfulness dan literasi kearifan lokal. Hubungan paling kuat ditemukan antara scientific culture Understanding dan literasi kearifan lokal, sedangkan kontribusi digital mindfulness tergolong lemah namun signifikan. Nilai R² untuk literasi biologi sebesar 0.440 mengindikasikan kontribusi model yang moderat. Kesimpulan penelitian ini menegaskan pentingnya integrasi pendekatan budaya, teknologi, dan ilmiah dalam pembelajaran biologi di pendidikan tinggi. Penelitian ini memberikan kontribusi teoritis terhadap pengembangan literasi sains berbasis konteks lokal serta rekomendasi praktis bagi pendidik dan pengambil kebijakan dalam merancang kurikulum yang berkualitas dan efektif.